Bilingualism and symbolic abstraction: Implications for algebra learning. (June 2017) - Mielicki, Marta K.; Kacinik, Natalie A.; Wiley, Jennifer
Abstract: Much of the research on bilingualism and math learning focuses on the potential challenges that bilinguals and language learners may face. The current line of research took an alternative approach and explored whether a bilingual advantage may emerge for a novel algebraic problem solving task that requires symbolic thought, the Symbol Math task. No differences were seen between bilingual and monolingual samples on basic math or executive control tasks; however, a bilingual advantage was seen in performance on the Symbol Math task across two experiments. The results suggest that bilingualism may improve the ability to engage in more abstract or symbolic thought processes, which may have important implications for algebra learning. Highlights: Two studies compared monolingual and bilingual young adults in different measures. Bilinguals outperformed monolinguals on a novel algebraic problem solving task. No differences were found in executive control for monolinguals and bilinguals. Results suggest a bilingual advantage in learning or applying novel symbolic rules.